Future Leaders: A Journey in Leadership Development for Vocational School Students - Setiawan, Dimas (Journal of TVET and Technology Review, 2024)
This systematic review article focuses on the leadership development for vocational school students. Generally, students lack self-development in leadership but rather the following the organization. Unfortunately, most past research was not from the perspectives of the social science and education community. Hence, the present study reviewed many past studies on leadership development for vocational school students. Meanwhile, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was adopted for the review of the current research which utilized two main journal databases, namely Scopus and Science Direct. Accordingly, the search efforts resulted in a total of 20 articles that can be analyzed systematically. Most importantly, the review managed to formulate three main themes, namely the need for leadership in vocational schools, the integration of leadership in vocational curriculum, and the last is success stories and best practices. Finally, many recommendations were presented at the end of this research for the reference of future scholars.